Imperfections of supervisory prudential regulations related to credit exposures secured by mortgages - Wiszniowski, Edward (Niedoskonałości nadzorczych regulacji ostrożnościowych w zakresie ekspozycji kredytowych zabezpieczonych hipotecznie, 2018)
The credibility of economic information provided by banks is one of the key elements of building trust between the institutions and the economic environment. The activities of the national banking sector, due to the special responsibility for the entrusted deposits, is subject to restrictive legal regulations and is controlled by the banking supervision. The legal act binding the banks and regulating, among others, the rules of credit risk measurement derived from mortgage-secured loans is the S Recommendation which was issued by the Financial Supervision Commission. The publication discusses the imperfections of this supervisory regulation with regard the defined concepts and recommended methods for the measurement of credit exposure, the interpretation and the method of determining the value of mortgage security and LtV
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 1, s. 75-88
Keywords: LtV; mortgage security; real estate; credit risk; S Recommendation; zabezpieczenie hipoteczne; nieruchomości; ryzyko kredytowe; Rekomendacja S